Pengaruh Budaya Organisasi, Stres Kerja Terhadap Kinerja Karyawan dan Kepuasan Kerja Sebagai Variabel intervening (Studi Empiris Pada PT Panca Putra) - Karo-karo, Alex P.; Ongsa, Rezeki (Lembaga Riset Ilmiah, 2022)
The purpose of the study entitled The influence of organizational culture and work stress on employee performance and to determine the role of job satisfaction in the relationship between organizational culture, work stress and employee performance of PT Panca Putra. This study uses 102 respondents, the analytical technique used is a path analysis technique (parth analysis) using the SPSS version 17.0 program. And the results of the study indicate that organizational culture variables affect employee performance, job stress affects employee performance, job satisfaction mediates the influence of organizational culture and employee performance. Job satisfaction mediates the effect of job stress and employee performance. Although the results are getting smaller after employee satisfaction mediates.